Prehospital Spinal Immobilization: Effect of Effort on Kinematics of Voluntary Head-neck Motion Assessed using Accelerometry. Issue 1 (17th December 2015) - Pryce, Rob; McDonald, Neil
Abstract: Introduction: Standards for immobilizing potentially spine-injured patients in the prehospital environment are evolving. Current guidelines call for more research into treatment practices. Available research into spinal immobilization (SI) reveals a number of limitations. Problem: There are currently few techniques for measuring head and neck motion that address identified limitations and can be adapted to clinically relevant scenarios. This study investigates one possible method. Methods: Study participants were fitted with miniaturized accelerometers to record head motion. Participants were exposed to three levels of restraint: none, cervical-collar only, and full immobilization. In each condition, participants were instructed to move in single planes, with multiple iterations at each of four levels of effort. Participants were also instructed to move continuously in multiple planes, with iterations at each of three levels of simulated patient movement. Peak and average displacement and acceleration were calculated for each immobilization condition and level of effort. Comparisons were made with video-based measurement. Participant characteristics also were tracked. Results: Acceleration and displacement of the head increased with effort and decreased with more restraint. In some conditions, participants generated measurable acceleration with minimal displacement. Continuous, multi-dimensional motions produced greater displacement and acceleration than single-plane motions under similar conditions. Conclusion: Study results suggest a number of findings: acceleration complements displacement as a measure of motion in potentially spine-injured patients; participant effort has an effect on outcome measures; and continuous, multi-dimensional motion can produce results that differ from single-plane motions. Miniaturized accelerometers are a promising technology for future research to investigate these findings in realistic, clinically relevant scenarios. R Pryce, N McDonald .Prehospital spinal immobilization: effect of effort on kinematics of voluntary head-neck motion assessed using accelerometry .Prehosp Disaster Med .2016 ;31 (1 ):36 –42 .